Radical surgery on the middle ear in the treatment of cholesteatoma: history or reality? A review - Vadim S. Isachenko; Vladimir V. Dvorianchikov; Sergey Y. Ognetov; Kseniya I. Sotnikova; Dolgorma A. Tsydypova (Consilium Medicum, 2023)
Radical surgery on the middle ear is primarily associated with such pathology as cholesteatoma and ear neoplasms. And if in the case of tumors radicalism in ear surgery is justified, then in the surgery of the cholesteatomic process there is a need to discuss this issue. The existence of acquired cholesteatoma was recognized more than three centuries ago. Without timely detection and intervention, cholesteatomas can increase to gigantic sizes and lead to numerous intracranial and extracranial complications. Due to its aggressive growth, invasive nature and potentially fatal consequences of intracranial complications, acquired cholesteatoma remains the cause of morbidity and death in those who do not have access to advanced medical care. Currently, there are no effective non-surgical methods of treatment. The article provides a brief overview of the main issues related to acquired middle ear cholesteatoma, and discusses the practical